Strategi Pengembangan Usaha Kerupuk Ikan di Air Gading Kecamatan Baturaja Barat Kabupaten Ogan Komering Ulu - Endang Lastinawati (KaliAgri Journal, 2025)
The cracker industry is one of the food industries that has been widely known by the people in Indonesia. This study aims to formulate a strategy for developing a cracker business in OKU Regency. The study was conducted using a case study method at the Doa Ibu Fish Cracker Business. Strategy formulation was carried out using the SWOT method. The results of the study provide recommendations for the Doa Ibu cracker business development strategy consisting of: 1) SO Strategy (cracker business owners should maintain the business they run because demand is increasing and can open up good business opportunities); 2) ST Strategy (looking for opportunities that provide benefits, increasing understanding in improving the business so that production is met); 3) WO Strategy (the need for more capital can provide a developed business in the city and outside the city, and increase sales promotion); and 4) WT Strategy (cracker business owners should add employees to increase cracker production and be able to quickly sell more).